2005
DOI: 10.1093/jxb/eri296
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene biosynthesis and perception in apple fruitlet abscission (Malus domestica L. Borck)

Abstract: Abscission was studied in immature apple fruits (cv. Golden Delicious) during the physiological drop. Fruitlet populations, characterized by different abscission potential, were analysed. Non-abscising fruitlets (NAF) were obtained from central flowers borne in clusters where all the lateral flowers had been removed at bloom while abscising fruitlets (AF) were derived from lateral fruitlets of trees sprayed with benzylaminopurine (BAP) at 200 ppm, 17 d after petal fall (APF), when the fruit cross diameter was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
45
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(55 citation statements)
references
References 31 publications
8
45
1
1
Order By: Relevance
“…Finally, 5 lL of the PCR product were run in 1.5% agarose gel colored by Sybrgreen (Sigma-Aldrich) and visualized under UV light. Seven reference genes such as GAPDH [3], 18S rRNA [3], S19 [3], Ubiquitine [2], Rubisco [4], RNA polymerase [4] and b-actine [9] as well as for the two viruses ASGV and ApMV [12] were chosen. These internal genes are known as the most stable expression in apple tissues Table 1.…”
mentioning
confidence: 99%
“…Finally, 5 lL of the PCR product were run in 1.5% agarose gel colored by Sybrgreen (Sigma-Aldrich) and visualized under UV light. Seven reference genes such as GAPDH [3], 18S rRNA [3], S19 [3], Ubiquitine [2], Rubisco [4], RNA polymerase [4] and b-actine [9] as well as for the two viruses ASGV and ApMV [12] were chosen. These internal genes are known as the most stable expression in apple tissues Table 1.…”
mentioning
confidence: 99%
“…The studies performed on this species pointed out that auxin, ethylene and their interaction are of primary importance [12,13]. Briefly, it was previously found that a massive increase in MdACO1 transcript amount was concomitant with an increase in elements involved in the signal transduction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, it was previously found that a massive increase in MdACO1 transcript amount was concomitant with an increase in elements involved in the signal transduction pathway. Furthermore, the variation in transcript amount followed the increase in ethylene evolution [12]. In Arabidopsis, tomato, rice and several other species these genes are present as multigene families whose members may have specific functions depending on the tissue and/or developmental stage [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of these ethylene receptors have focused on understanding their roles in apple shelf life by quantifying the levels of their mRNA and/or protein accumulation (Tatsuki & Endo, 2006;Tatsuki, Endo, & Ohkawa, 2007;Tatsuki, Hayama, & Nakamura, 2009;Wang et al, 2009;Wiersma et al, 2007). The transcript levels of MdETR1 and MdERS1 were also evaluated in a study of ethylene biosynthesis and perception in apple fruitlet abscission (Dal Cin, Danesin, Boschetti, Dorigoni, & Ramina, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only MdCTR1 has been described in apple. The conserved 3' end of the MdCTR1 coding region (AY670703) was cloned by Dal Cin et al (2005). Its full length cDNA was characterized by several alternative splicing variants (DQ847147-DQ847149) (Wiersma et al, 2007).…”
Section: Introductionmentioning
confidence: 99%